2017
DOI: 10.1037/dev0000276
|View full text |Cite
|
Sign up to set email alerts
|

Pathways between self-esteem and depression in couples.

Abstract: Guided by concepts from a relational developmental perspective, this study examined intra- and interpersonal associations between self-esteem and depressive symptoms in a sample of 1,407 couples surveyed annually across 6 years in the Panel Analysis of Intimate Relations and Family Dynamics (pairfam) study. Autoregressive cross-lagged model results demonstrated that self-esteem predicted future depressive symptoms for male partners at all times, replicating the vulnerability model for men (low self-esteem is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 66 publications
4
21
1
3
Order By: Relevance
“…Studies confirm a significant relationship between positive dyadic coping and higher relational satisfaction and the quality of relationships (Bodenmann et al 2006(Bodenmann et al , 2007Falconier et al 2013b;Iafrate et al 2012;Kardatzke 2009;Randall and Bodenmann 2017). Studies on dyadic coping carried out on clinical populations showed that positive dyadic coping had the potential to reduce depressive symptoms Gabriel et al 2016;Johnson et al 2017) and strengthen the quality of the relationship (Beach et al 2014). Breast cancer patients and partners who presented more common dyadic coping declared higher relational satisfaction (Badr et al 2010) and negative behaviors were associated with depressed mood for both patients and their partners (Rottmann et al 2015).…”
Section: Introductionmentioning
confidence: 93%
“…Studies confirm a significant relationship between positive dyadic coping and higher relational satisfaction and the quality of relationships (Bodenmann et al 2006(Bodenmann et al , 2007Falconier et al 2013b;Iafrate et al 2012;Kardatzke 2009;Randall and Bodenmann 2017). Studies on dyadic coping carried out on clinical populations showed that positive dyadic coping had the potential to reduce depressive symptoms Gabriel et al 2016;Johnson et al 2017) and strengthen the quality of the relationship (Beach et al 2014). Breast cancer patients and partners who presented more common dyadic coping declared higher relational satisfaction (Badr et al 2010) and negative behaviors were associated with depressed mood for both patients and their partners (Rottmann et al 2015).…”
Section: Introductionmentioning
confidence: 93%
“…Level of depression symptoms is a widely used indicator of psychological problems and can be used to approximate respondents' overall mental health status. This indicator is also measured within couples (Johnson et al 2017). Partnership expectations are directly correlated to individuals' previous and subsequent partnership careers.…”
Section: Research Strategy and Hypothesesmentioning
confidence: 99%
“…Doświadczanie rozpadu związku zmniejsza poczucie własnej wartości, rezultat ten jednak znika po 1 roku, nawet jeśli badany pozostaje sam. Wysoka samoocena pozwala na przewidywanie możliwości wejścia w związek, a niska samoocena zwiększa prawdopodobieństwo rozpadu związku -być może za sprawą mediującej roli jakości komunikacji (Luciano, Orth, 2017;Johnson, Galambos, Finn, Neyer, Horne, 2017). Doniesienia z badań wskazują również na znaczenie ogólnej samooceny bezpośrednio dla jakości życia seksualnego.…”
Section: Dorota Suwalska-barancewicz Alicja Malinaunclassified